2010
DOI: 10.1016/j.toxicon.2009.06.032
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heparin treatment on the expression and activity of different ion-motive P-type ATPase isoforms from mouse extensor digitorum longus muscle during degeneration and regeneration after Bothrops jararacussu venom injection

Abstract: Ca(2+) ions are essential to myonecrosis, a serious complication of snake envenomation, and heparin seems to counteract this effect. We investigated the effect of local injection of Bothrops jararacussu venom in mouse fast-twitch extensor digitorum longus (EDL) muscle, without or with heparin, on functional/molecular alterations of two central proteins involved in intracellular Ca(2+) homeostasis, sarco(endo)plasmic reticulum Ca(2+)-ATPase (SERCA) and Na(+)/K(+)-ATPase. EDL-specific SERCA1 isoform expression d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The prevalence of snakebites in Latin America is inflicted largely by pit vipers belonging to Viperidae, subfamily Crotalinae, and species of the Bothrops genus [3,4]. In Brazil, envenoming by ophidian accidents is a societal burden, mainly affecting workers of the deep countryside [5]. The hands, ankles, and legs are the body regions more subjected to bites of snakes, and skeletal muscle is the main tissue affected by Bothropic envenomation.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of snakebites in Latin America is inflicted largely by pit vipers belonging to Viperidae, subfamily Crotalinae, and species of the Bothrops genus [3,4]. In Brazil, envenoming by ophidian accidents is a societal burden, mainly affecting workers of the deep countryside [5]. The hands, ankles, and legs are the body regions more subjected to bites of snakes, and skeletal muscle is the main tissue affected by Bothropic envenomation.…”
Section: Introductionmentioning
confidence: 99%
“…For example, during early but not late stages of embryogenesis mammals regenerate their skin wounds without scars. 7 Mazzalupo and colleagues have shown that when a wound is induced in the skin of a normal developing mouse between embryonic days of development [11][12][13][14] (E11-E14), the wound completely closes and fully regenerates in less than 18 hours after wound induction. In contrast, when the wound is induced after embryonic day E14.5-adulthood, the wound closure is delayed, is not able to regenerate and a scar is formed instead.…”
Section: Pmp Plasma Membrane Potential Rel Relative Expression Levelmentioning
confidence: 99%
“…This suggests that H+ flux serves as “high‐level master regulator” that initiates very complex and coherent downstream growth and patterning events . The role of ion channels, in promoting scarless wound healing and/or regeneration in mammals however is not yet defined except for the role of one ion channel gene, SERCA, implied in muscle regeneration …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…ATPase activity was evaluated colorimetrically by measuring the amount of inorganic phosphate (Pi) released from ATP hydrolysis as reported [68]. The assay was performed at 37°C for 1 h. The reaction was started by adding 10 µg protein of each preparation to a medium consisting of 84 mM NaCl, 3 mM MgCl 2 , 3 mM ATPNa 2 , 10 mM NaN 3 , 1 mM EGTA, and 20 mM maleate-Tris buffer, pH 7.4, with 10 mM KCl (total activity) or 1 mM ouabain (ouabain-resistant activity).…”
Section: Na + /K + -Atpase Activity Assaymentioning
confidence: 99%